Study on the Influence of Bionic Structure on the Sealing Performance of Centrifugal Pump Sealing Ring - Ye Cai; Zhengpu Xie; Feixiang Yang; Muhan Yan; Chengqi Mou; Zhangcheng Huang; Yuxin Jin; Jiegang Mou; Yunqing Gu (Lubricants)
In order to improve the sealing performance of a sealing ring in order to improve the efficiency of the centrifugal pump, based on the bionics principle, a calculation model for the bionic groove surface sealing ring structure of the centrifugal pump is established, based on the Realizable k-ε turbulence model. The external characteristics, internal flow field distribution and leakage characteristics of centrifugal pumps with different bionic groove surface structures and groove diameters are analyzed, and the influence of bionic surface structure on the sealing performance of the centrifugal pump sealing ring is studied. The results show that the bionic groove structure has a certain promoting effect on the external characteristics of the pump; a sealing ring with a circular groove structure can improve the efficiency, greatly reduce the leakage, and has better sealing performance, which are important influences on the performance and stability of the centrifugal pump. Among the three different diameters of the circular groove, the optimal groove diameter of the surface structure is 0.2 mm, where leakage is the least, volume efficiency is the largest, and sealing performance is the best.